Enhancing the capacity of tourism awareness groups in destination development in Paser Regency - Ulfah, Yana; Rahmawati, Rahmawati; Abidin, Zainal; Arifin, Zainal; Darma, Dio Caisar; Kustiawan, Andriawan (Universitas Muhammadiyah Magelang, 2025)
This community service activity aimed to improve the managerial capacity and participation of Tourism Awareness Group (POKDARWIS) members in tourism destination development, and to increase local community income in Paser Regency. The program focused on six crucial aspects: identification and planning, governance, marketing and promotion, product revitalization, sustainability and preservation, and evaluation and adaptation. Conducted through three main stages—preparation, dissemination, and evaluation—the activity utilized a comprehensive training methodology. Evaluation results indicated a significant increase in POKDARWIS members' knowledge regarding aspects of tourism destination development, as evidenced by paired sample t-tests (p<0.05). Furthermore, there was an increase in awareness regarding tourism management, community participation, and understanding of potential income from tourism activities. This suggests the effectiveness of the dissemination program in strengthening the function of POKDARWIS for sustainable tourism development in Paser Regency.